2022
DOI: 10.3389/fmicb.2021.808938
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacillus velezensis Strain P2-1 for Biocontrol of Apple Postharvest Decay Caused by Botryosphaeria dothidea

Abstract: Botryosphaeria dothidea causes apple ring rot, which is among the most prevalent postharvest diseases of apples and causes significant economic loss during storage. In this study, we investigated the biocontrol activity and possible mechanism of Bacillus velezensis strain P2-1 isolated from apple branches against B. dothidea in postharvest apple fruit. The results showed strain P2-1, one of the 80 different endophytic bacterial strains from apple branches, exhibited strong inhibitory effects against B. dothide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…9,68 B. amyloliquefaciens SF14 and SP10 not only produced antifungal lipopeptides bacillomycin, fengycin, iturin, and surfactin but also lytic enzymes with amylase, protease, and cellulase activities (Figure 1B), 125 whereas B. velezensis P2-1 was able to synthesize lipopeptides and polyketides and simultaneously induce disease resistance in postharvest apples. 126 This indicates that some strains can simultaneously use different mechanisms of action. Sawant et al reported that B. amyloliquefaciens DRo-198 and TS-204 were able to produce enzymes with cellulase, β-1,3-glucanase, and chitinase activities.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…9,68 B. amyloliquefaciens SF14 and SP10 not only produced antifungal lipopeptides bacillomycin, fengycin, iturin, and surfactin but also lytic enzymes with amylase, protease, and cellulase activities (Figure 1B), 125 whereas B. velezensis P2-1 was able to synthesize lipopeptides and polyketides and simultaneously induce disease resistance in postharvest apples. 126 This indicates that some strains can simultaneously use different mechanisms of action. Sawant et al reported that B. amyloliquefaciens DRo-198 and TS-204 were able to produce enzymes with cellulase, β-1,3-glucanase, and chitinase activities.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The V. pyri, Valsa mali, C. gloeosporioides and Botryosphaeria dothidea strains used for the present study (Yuan et al, 2022) were cultured in potato dextrose agar (PDA; potato extracts 200 g L −1 , glucose 20 g L −1 , and agar 15 g L −1 ) and grow at 25°C.…”
Section: Pathogenic Fungal Isolatesmentioning
confidence: 99%
“…Healthy one-year-old branches were harvested in June 2021 from an "Enli" pear tree in Zhengzhou (Henan province, China) to isolate endophytic bacteria with the procedure as the same as reported previously (Yuan et al, 2022). The ability of all isolated endophytes to inhibit the growth of V. pyri was assessed using a dual culture screening approach as detailed previously by Yuan et al (2022).…”
Section: Isolation and Screening Of Potentially Antagonistic Bacteriamentioning
confidence: 99%
See 2 more Smart Citations